Gut Microbiota in Untreated Diffuse Large B Cell Lymphoma Patients - Yuan, Li; Wang, Wei; Zhang, Wei; Zhang, Yan; Wei, Chong; Li, Jingnan; Zhou, Daobin (Frontiers in Microbiology, 2021)
Intestinal microecology plays an important role in the development and progression of hematological malignancies. However, characteristics of gut microbiota in diffuse large B cell lymphoma (DLBCL) have not been reported. The microbiota composition of fecal samples from 25 untreated DLBCL patients and 26 healthy volunteers was examined by 16s rRNA gene sequencing. On α-diversity analysis, there was no significant difference in species diversity and abundance between the two groups. However, a significant difference was observed on β-diversity analysis. The intestinal microbiota in patients with DLBCL showed a continuous evolutionary relationship, which progressed from Phylum, proteobacteria, to Genus, Escherichia-Shigella. Their abundance was significantly higher than that of the control group. At the genus level, Allisonella, lachnospira and Roseburia were more abundant in patients with DLBCL than in the control group. Functional prediction by PICRUSt indicated that Thiamine metabolism, and Phenylalanine, tyrosine and tryptophan biosynthesis were significantly lower in the DLBCL group than in the control group. In conclusion, our results clearly demonsrate that the gut microbiota was changed significantly in DLBCL. The study highlights fundamental differences in the microbial diversity and composition of patients with DLBCL and paves the way for future prospective studies and microbiome-directed interventional trials to improve patient outcomes.